Μ-XRF Analysis of Trace Elements in Lapis Lazuli-Forming Minerals for a Provenance Study. (18th March 2015) - Angelici, Debora; Borghi, Alessandro; Chiarelli, Fabrizia; Cossio, Roberto; Gariani, Gianluca; Lo Giudice, Alessandro; Re, Alessandro; Pratesi, Giovanni; Vaggelli, Gloria
Abstract: This paper presents new developments on the provenance study of lapis lazuli started by our group in 2008: during the years a multi-technique approach has been exploited to obtain minero-petrographic characterization and creation of a database considering only rock samples of known provenance. Since the final aim of the study is to develop a method to analyze archeological findings and artworks made with lapis lazuli in a completely non-invasive way, ion beam analysis techniques were employed to trace the provenance of the raw material used for the production of artifacts. Continuing this goal and focusing the analysis on determination of more significant minero-chemical markers for the provenance study of trace elements in different minerals, the method was extended with the use of micro X-ray fluorescence ( µ -XRF), to test the potential of the technique for this application. The analyzes were focused on diopside and pyrite in lapis lazuli samples of known provenance (Afghanistan, Tajikistan, and Siberia). In addition, µ -XRF data were compared with micro proton-induced X-ray emission ( µ -PIXE) results to verify the agreement between the two databases and to compare the analytical performance of both techniques for this application.